Intermediate crack induced debonding in steel beams reinforced with CFRP plates under fatigue loading. (15th September 2018) - Bocciarelli, Massimiliano; Colombi, Pierluigi; D'Antino, Tommaso; Fava, Giulia
Highlights: Artificially notched steel beams strengthened by using CFRP materials under fatigue loads are considered. An analytical model to evaluate the CFRP axial force and the debonded zone length is proposed. A numerical finite element model, employing a damage cohesive interface, was presented. A good agreement was found among the analytical, numerical and experimental results. A parametric analysis was performed to investigate the influence of some parameters on the CFRP strain distribution. Abstract: Externally adhesively bonded Carbon Fibre Reinforced Polymers (CFRP) plates are often regarded as an effective technique to strengthen notched steel beams. However, the possible CFRP intermediate debonding may drastically reduce the reinforced steel beam strength against fatigue crack propagation. It is assumed that, for the beam geometry and materials under analysis, the fatigue load does not directly cause debonding, but it may trigger steel crack propagation, leading to the onset of debonding. In this paper, analytical and numerical models for elasto-brittle adhesives were proposed to evaluate the stress and strain distribution in the reinforcement for a given crack length. The outcomes of experimental campaigns from the literature were considered to validate the proposed numerical and analytical techniques. A good agreement was found among the analytical, numerical and experimental results in terms of strain distribution in the CFRP material, showing the accuracy of the proposed models. Finally, a parametric analysis was performed to investigate the influence of some parameters on the CFRP strain distribution.